Enhancing soybean growth, yield, and seed protein by TiO2 nanoparticles and Brevibacterium sediminis under drought stress - Kaniz Fatema Jui; Md A. Mannan; Md Abdul Karim; Masuma Akter; Most. Tanjina Akter; Dipanjoli Baral Dola; Aysha Siddika Jarin; Md Tofazzal Islam (Heliyon)
Drought stress poses a significant challenge to soybean (Glycine max) production, necessitating the development of effective strategies to improve growth and yield in such conditions. This study investigates the individual and combined effects of the plant probiotic bacterium Brevibacterium sediminis (Bs) and titanium dioxide nanoparticles (TiO2, NPs) on soybean plants subjected to drought stress. The experimental design included two primary factors: Factor A (water treatment) with i) well-watered conditions at 80 % of field capacity (FC) and ii) drought conditions at 40 % of FC, and Factor B consisting of six treatments: i) control (no treatment), ii) foliar application of 200 ppm TiO2 NPs, iii) foliar application of 400 ppm TiO2 NPs, iv) seed priming with Bs, v) seed priming with Bs and 200 ppm TiO2 NPs (Bs + 200 ppm TiO2 NPs), and vi) seed priming with Bs and 400 ppm TiO2 NPs (Bs + 400 ppm TiO2 NPs). The pot experiment was conducted under a polyhouse using a completely randomized design (CRD) with three replicates. Our findings indicate that both TiO2 NPs and B. sediminis, whether applied individually or in combination, significantly enhanced growth, physiological parameters, yield, and seed protein content in drought-stressed soybean plants compared to untreated control. The most pronounced effects were observed with the combination treatment of 400 ppm TiO2 NPs and B. sediminis, resulting in increases of 30.70 % in plant height and 83.46 % in total plant dry weight compared to untreated drought conditions. Additionally, compared to untreated drought stressed soybean plants, this combined treatment improved relative water content, photosynthetic rate, total chlorophyll levels, membrane stability index, proline, antioxidant activity (DPPH), seed yield, and seed protein content by 43.42 %, 17.89 %, 55.23 %, 45.04 %, 47.89 %, 66.63 %, 74.39 %, and 11.14 %, respectively. Correspondingly, levels of malondialdehyde and hydrogen peroxide decreased by 28.48 % and 58.53 %, respectively compared to untreated drought conditions. These results collectively suggest that the foliar application of 400 ppm TiO2 NPs, in conjunction with seed priming using B. sediminis, significantly enhances soybean productivity under drought conditions. Future research should explore the molecular mechanisms that underpin these beneficial and synergistic effects of TiO2 NPs and B. sediminis in soybean cultivation under water-limited environments.